1999
DOI: 10.1366/0003702991945209
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Fourier Transform Mass Spectrometry of Macromolecules: The First Decade

Abstract: Susumu Tanimura (left), Michiaki Kohno (right), and colleagues investigate how SH3P2, a downstream target of the ERK signaling pathway, inhibits cell migration. The researchers fi nd that the class I myosin Myo1E is a binding partner of SH3P2 and that ERK signaling disrupts SH3P2's association with Myo1E, allowing the myosin to relocalize from the cytosol to the tips of lamellipodial protrusions at the leading edge of the cell. There, Myo1E promotes lamellipodial extension and cell motility. In serum-starved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…' Fenn's contribution was the development of electrospray ionization (ESI) (Fenn et al, 1989). The combination of ESI with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) (Henry et al, 1989;Hendrickson & Emmett, 1999;Lorenz, Maziarz, & Wood, 1999) is a powerful tool for biomolecular analysis. ESI allows the analysis of ions of more than 100,000 Da in mass (Chen et al, 1995) while retaining optimum FT-ICR performance because of the typically observed low (below 4,000) mass-to-charge ratios.…”
Section: Introductionmentioning
confidence: 99%
“…' Fenn's contribution was the development of electrospray ionization (ESI) (Fenn et al, 1989). The combination of ESI with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) (Henry et al, 1989;Hendrickson & Emmett, 1999;Lorenz, Maziarz, & Wood, 1999) is a powerful tool for biomolecular analysis. ESI allows the analysis of ions of more than 100,000 Da in mass (Chen et al, 1995) while retaining optimum FT-ICR performance because of the typically observed low (below 4,000) mass-to-charge ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The electrospray source conditions can also influence the conformational distribution of the protein ions. These parameters include capillary temperature, source pressure and voltage [7,8].…”
mentioning
confidence: 99%
“…Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) [10] provides the highest mass resolution, highest mass resolving power, and highest mass accuracy (low ppm). When combined with electrospray ionization (ESI), FT-ICR MS [11,12] provides high analytical sensitivity requiring femtomoles or less of sample [13,14]. High resolution FT-ICR MS permits mass measurement of large peptides (>3000 Da) with a mass accuracy of a few ppm.…”
Section: Introductionmentioning
confidence: 99%